PROPERTIES OF SOME SETS OF SEQUENCES DEFINED BY A MODULUS FUNCTION - Altin, Yavuz (Elsevier Science Inc, 2009)
In this article, the author introduces the generalized difference paranormed sequence spaces c(Delta(m)(upsilon), f, p, q, s), c(0) (Delta(m)(upsilon), f, p, q, s), and l(infinity)(Delta(m)(upsilon), f, p, q, s) defined over a seminormed seqnence space (X, q). The author also studies their properties like completeness, solidity, symmetricity, etc.
Keywords: Difference sequence; modulus function; seminorm